Understanding Legal Aspects in E-Commerce as an Effort for Economic Recovery in Kare Village, Kare District, Madiun Regency - Miko Aditiya Suharto (Faculty of Law, 2022)
The COVID-19 pandemic has a destructive impact on Micro, Small, and Medium Enterprises (MSME). In order to increase the income in Kare Village, Madiun Regency, various efforts have been made by the Regional Government, including providing Micro Business Productive Assistance and registering several MSME actors in the MSME Virtual Expo exhibition. The service activity of e-commerce is carried out using the method of socialization and question and answer with the Tourism Awareness Group and several MSME actors in Kare Village related to providing Contract Basics for MSME Actors, Consumer Protection Law, and the use of e-commerce in improving the economy in the future. The use of e-commerce today can no longer be arbitrary; several rules need to be understood by the public so as not to slip into legal problems. So MSME actors must understand the basics of agreement law and e-commerce. MSME actors in Kare Village can still promote and sell tourism products in the Kare Village area even though they are in the Enforcement of Community Activity Restrictions through website applications and social media such as Tokopedia and Instagram. Understanding the legal basics of e-commerce provides preventive efforts for MSME actors in Kare Village to minimize the occurrence of unlawful acts. Utilizing the website and social media for Kare Village tourism which is implemented based on applicable legal regulations for Kare Village MSME actors to restore the village economy so that the goal of Kare village to create Ecotourism can be realized.